Perkin-Elmer fluorescence spectrophotometer in use for cancer research - Perkin-Elmer Corporation (1970)
General view of a sample of anti-cancer drug metabolite being inserted into the cell of a Perkin-Elmer fluorescence spectrophotometer at an unidentified laboratory facility. The woman visible in the photograph is identified as Marianne Callahan of the Biomolecular Sciences Section of the Arthur D. Little company, an international management consulting firm. Per notations accompanying the photograph, the sample is being analyzed to determine how it behaves in a biological system, part of the company's work concerning drug therapy recommendations for the National Cancer Institute.
Keywords: Perkin-Elmer Corporation; Scientific apparatus and instruments; Spectrophotometer; Corporations; Arthur D. Little, Inc.; Drugs; Drugs--Research; Cancer--Research; Women employees; Fluorescence spectroscopy; Laboratories; Employees